RHETORICAL APPEALS OF PASTOR STANLEY AND AHMED DEEDAT IN GREAT OPEN “IS BIBLE GOD’S WORD?” (A PRAGMATIC STUDY) - Andi Tenri Abeng; Hardiana Hardiana (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2021)
The aims of the research are to reveal rhetorical appeals between Pastor Stanley and Ahmed Deedat in great open “Is Bible God’s word?”. And the writing used the qualitative method. Basically, it’s made by some references of books and also some articles by another source like website or blog, not only to support this writing but can ensure that it has any relation with the topic. The research applied the library research through pragmatic approach that study speech act, implicature and rhetorical creating technique. In this case, between Pastor Stanley and Ahmed Deedat. The primary data was taken from debate video Pastor Stanley and Ahmed Deedat in great open “is Bible God’s word?” Then analyzed by applying descriptive qualitative method. The result shows that rhetorical appeal and some pragmatic elements in the debate video between Pastor Stanley and Ahmed Deedat is showed by using structural words or sentences in the debate video itself. It also shows three elements of rhetoric, namely ethos, phatos, logos, which are used by the two speakers in the video.